All-terrain experts: Land surveyors, remote mapping and land alienation in Mendoza, Argentina - Facundo Martín (Freie Universität Berlin, Junior Research Group 'Global Change - Local Conflicts' (GLOCON), 2019)
There has been recent growing interest in the role of expert knowledge around land politics. One area that has often been overlooked is how land-related expert knowledge has fostered the transformation of the regime of land control, access and ownership. This paper aims to capture the distinctiveness of contemporary mapping politics in relation to the commodification of land by corporate and state actors. I analyse how remote mapping practices influence the transformation of land regimes. The main research question is how and to what extent land surveyors and their cadastral mapping practices facilitate and legitimate market-led land commodification, and at the same time contribute to de jure and de facto peasant land alienation. – – In jüngster Zeit rückte die Bedeutung von Expert_innenwissen für Landpolitik vermehrt ins Blickfeld der akademischen Debatte. Bislang wird hierbei jedoch die Rolle von Expert_innenwissen bei der Transformation von Kontrolle über, Zugang zu und Besitz von Land oftmals übersehen. Ziel dieses Beitrags ist daher, die Besonderheiten und die Bedeutung gegenwärtiger Kartographierung von Land hinsichtlich dessen Kommodifizierung durch Unternehmen und staatliche Akteur_innen herauszuarbeiten. Ich analysiere, wie remote mapping practices die Transformation von Landregimen beeinflussen. Die zentrale Forschungsfrage lautet wie und inwieweit Landvermesser_innen und deren Kartierungspraktiken für die Katasterämter die Kommodifizierung von Land erleichtern und legitimieren und gleichzeitig de jure und de facto zur Veräußerung von Land von Kleinbäuerinnen und Kleinbauern beitragen.
Keywords: 330; Critical cartography; land politics; experts; cadastral mapping; Kritische Kartographie; Landpolitik; Expert_innen; Katasterkartierung